Efisiensi Teknis Industri BPR di Eks Karesidenan Pati - Nurul Komaryatin (Jurnal Ilmiah Aset, 2008)
Finances sector, foremost banking industries have important relo economy activities. Its role is as financial intermediary connecting (lenders) or surplus unit to and an entrepreneur in other side.Bank technique can be measured by counting ratio between banking output and input. Data Envelopment Analysis (DEA) will count bank which use input n to produce different ouput. The results of technique efficiency research BPR in Ex Karisidenan Pati using data tabulation DEA-CRS Merger of BPR BKK in each Kabupaten is hoped to increase efficiency rate in each BPR in Kabupaten Ex Karisedanan Pati. By merger, efficiency value will increase if compared with BPR before they margered.